The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1038/s41598-021-81365-7
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of SteraMist ionized hydrogen peroxide technology in the sterilization of N95 respirators and other PPE

Abstract: The COVID-19 pandemic has led to widespread shortages of personal protective equipment (PPE) for healthcare workers, including of N95 masks (filtering facepiece respirators; FFRs). These masks are intended for single use but their sterilization and subsequent reuse has the potential to substantially mitigate shortages. Here we investigate PPE sterilization using ionized hydrogen peroxide (iHP), generated by SteraMist equipment (TOMI; Frederick, MD), in a sealed environment chamber. The efficacy of sterilizatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…However, during the first SARS pandemic, the CDC stated that “health care facilities may consider reuse as long as the device has not been obviously soiled or damaged (e.g. creased or torn)” and “if a sufficient supply of respirators is not available [ 41 ].” Multiple mask decontamination methods were tested and implemented during the COVID-19 pandemic and have further expanded on this concept, including UV germicidal irradiation, vaporous and ionized hydrogen peroxide (VHP/iHP) and moist heat [ 42 – 49 ], all of which promise to enable N95 reuse (for instance, the FDA EUA for the Battelle decontamination system permits up to 20 vaporous hydrogen peroxide decontamination cycles per respirator [ 50 ]). However, mask reuse is generally limited by breakage or degradation of the malleable nose clips and other components that are bent to form a seal around a user’s nose and the elastic bands that hold a mask in place.…”
Section: Discussionmentioning
confidence: 99%
“…However, during the first SARS pandemic, the CDC stated that “health care facilities may consider reuse as long as the device has not been obviously soiled or damaged (e.g. creased or torn)” and “if a sufficient supply of respirators is not available [ 41 ].” Multiple mask decontamination methods were tested and implemented during the COVID-19 pandemic and have further expanded on this concept, including UV germicidal irradiation, vaporous and ionized hydrogen peroxide (VHP/iHP) and moist heat [ 42 – 49 ], all of which promise to enable N95 reuse (for instance, the FDA EUA for the Battelle decontamination system permits up to 20 vaporous hydrogen peroxide decontamination cycles per respirator [ 50 ]). However, mask reuse is generally limited by breakage or degradation of the malleable nose clips and other components that are bent to form a seal around a user’s nose and the elastic bands that hold a mask in place.…”
Section: Discussionmentioning
confidence: 99%
“…We were also unable to assess the efficacy of different methods for sterilizing PanFab PAPRs, but materials used in the designs are compatible with alcohol-based wipes (e.g., acrylonitrile butadiene styrene ( Industrial Specialties Mfg and IS MED Specialties, 2019 ) allowing CDC recommendations for disinfecting PAPRs to be followed ( CDC, 2020b ). Previous research also suggests that ionized hydrogen peroxide techniques would be compatible with PAPR sterilization ( Cramer et al, 2021 ). Additional usability, durability and sterilization testing await the availability of additional PAPR units assembled during production scale-up.…”
Section: Discussionmentioning
confidence: 99%
“…Investigation into sterilization methods include UV light, 12 steam, 13 humid heat, 14 autoclaves, 15 and hydrogen peroxide. 16 , 17 UV light has been used to scale production to 12,000 sanitized respirators per day. 18 Yale researchers found that hydrogen peroxide vapor could be used for five cycles on respirators without any deformation.…”
Section: Reuse Of Existing N95 Respiratorsmentioning
confidence: 99%